Implementation of the Deep Learning Model on Underhand Passing Skills in Volleyball Games at Elementary School - M Zaeni Nur Fuady; Encep Sudirjo; Anggi Setia Lengkana (Journal of Physical Education Health and Sport, 2026)
Physical education plays a crucial role in fostering students’ motor, cognitive, and social development at the elementary school level. In volleyball learning, underhand passing is a fundamental skill; however, many students experience difficulties due to conventional drill-based instruction that emphasizes repetition rather than conceptual understanding. This study aimed to examine the effectiveness of implementing the Deep Learning model in improving underhand passing skills among sixth-grade students at Elementary School Cikeusik Rancakalong. The research employed Classroom Action Research (CAR) based on the Kemmis and McTaggart spiral model, consisting of three cycles: planning, action, observation, and reflection. The subjects of the study were 33 sixth-grade students. Data were collected through underhand passing skill tests and structured observation sheets, then analyzed using descriptive quantitative analysis to determine the percentage of learning completeness in each cycle. The findings indicated a consistent and significant improvement in students’ learning outcomes. Learning completeness increased from 12.1% in the pre-cycle to 39.4% in Cycle I, 72.7% in Cycle II, and ultimately reached 90.9% in Cycle III, surpassing the predetermined classical mastery criterion. The results demonstrate that the Deep Learning model not only enhances technical execution but also strengthens students’ conceptual understanding, reflective thinking, and motor awareness. Students became more capable of identifying movement errors and adjusting body positioning effectively. In conclusion, the Deep Learning model provides a structured, student-centered, and reflective instructional approach that effectively improves underhand passing skills and contributes to the development of innovative and meaningful physical education practices in elementary schools.